Comparative repeatome analysis of Pyrgomorphidae and Acrididae (Orthoptera: Caelifera) revealed the contribution of repetitive DNA in genome gigantism - Muhammad Salman; Xuanzeng Liu; Nian Liu; Yuan Huang (PLoS ONE, 2025)
Eukaryotic genomes are often rich in DNA repetitive elements, involving both transposable elements (TE) and tandemly repeated satellite DNA. Grasshopper species, known for their large genome sizes, comprising relatively a high proportion of genomic repeats. This study aimed to identify and perform a comparative analysis of DNA repetitive content in eight grasshopper species from the Pyrgomorphidae and Acrididae families. We utilized unassembled low-coverage Illumina paired-end short reads in the RepeatExplorer2 pipeline to identify genomic repeats, and RepeatMasker to estimate their abundance and divergence activity. Flow cytometry estimated genome sizes, ranging from 1C = 7.670 pg to 18.612 pg, with Aularches miliaris (18.612 pg) being the second largest insect genome reported to date. The repeat content ranged from 51% to 74%, with a mean value of 64.26% of the total genome. The major identified repeat elements included LINE, Ty3_Gypsy, Penelope, Ty1-copia, Helitron, Maverick, and satellite repeats, with LINE elements being the most abundant, constituting 24% to 54% of the total repetitive content in Apalacris varicornis and A. miliaris, respectively. The positive correlation of repetitive content and TEs with genome size suggests that their expansion has contributed to the large genome sizes observed. Satellite DNA analysis identified 65 satDNA families across the eight species. Additionally, phylogenetic analysis of TE protein domains revealed that consensus sequences from the same domain cluster together, suggesting domain-specific evolutionary pathways for TEs in the genome. This study reveals new dynamics into the role of repetitive DNA in genome gigantism as well as other evolutionary mechanisms in the Pyrgomorphidae and Acrididae families of Orthoptera.